Prevalent Complications in Heart Transplantation: A Retrospective Cohort Analysis - Borzani, Gabriela Ribeiro (2024)
Objectives: To identify the prevalent complications after heart transplantation. Methods: This is a quantitative retrospectivecohort research with post-h eart transplant patients from 2010 to 2022 through medical record analysis. Results: Forty-nine postheart transplant patients participated in the study, six of whom died. The leading cause of heart failure before transplantation was idiopathic dilated heart failure (36.7%), followed by chagasic etiology (30.6%), with an average transplant waiting time of 7.4 months (standard deviation [SD] = 9.7). In the post-heart transplantation period, 95.9% of the population presented at least one complication, the most common being acute cellular rejection (81.6%), followed by cytomegalovirus infection (44.9%). Conclusion: The study provided relevant data to the literature to identify the prevalent complications in heart transplantation and implement nursing actions such as planning by nurses to improve self-management of care for transplant patients.